1990
DOI: 10.1093/geront/30.3.377
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Depression, and Family and Friendship Relations, on Residents' Loneliness in Congregate Housing

Abstract: We examined the impact of various social relationships on levels of loneliness reported by 208 elderly residents of 10 senior housing apartments. Because the literature demonstrates a clear relationship between depression and loneliness, this study controlled for depression to provide a more concise look at the condition of loneliness. Those who were less satisfied with the quality of their relationships and had less contact with close friends were more lonely. Whether one had children, grandchildren, siblings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 0 publications
7
71
0
Order By: Relevance
“…For instance, freshman who leave family and friends behind often feel increased social isolation when they arrive at college even though they are surrounded by large numbers of other young adults (e.g., (Cutrona, 1982;Russell, Peplau, & Cutrona, 1980). Lower levels of loneliness are associated with marriage (Hawkley, Browne, & Cacioppo, 2005;Pinquart & Sorenson, 2003), higher education (Savikko, Routasalo, Tilvis, Strandberg, & Pitkala, 2005), and higher income (Andersson, 1998;Savikko et al, 2005), whereas higher levels of loneliness are associated with living alone (Routasalo, Savikko, Tilvis, Strandberg, & Pitkala, 2006), infrequent contact with friends and family (Bondevik & Skogstad, 1998;Hawkley et al, 2005;Mullins & Dugan, 1990), dissatisfaction with living circumstances (Hector-Taylor & Adams, 1996), physical health symptoms (Hawkley et al, In press), chronic work and/or social stress (Hawkley et al, In press), small social network Mullins & Dugan, 1990), lack of a spousal confidant (Hawkley et al, In press), marital or family conflict (Jones, 1992;Segrin, 1999), poor quality social relationships (Hawkley et al, In press;Mullins & Dugan, 1990;Routasalo et al, 2006), and divorce and widowhood (Dugan & Kivett, 1994;Dykstra & De Jong Gierveld, 1999;Holmen, Ericsson, Andersson, & Winblad, 1992;Samuelsson, Andersson, & Hagberg, 1998).…”
Section: Structure and Spread Of Lonelinessmentioning
confidence: 99%
“…For instance, freshman who leave family and friends behind often feel increased social isolation when they arrive at college even though they are surrounded by large numbers of other young adults (e.g., (Cutrona, 1982;Russell, Peplau, & Cutrona, 1980). Lower levels of loneliness are associated with marriage (Hawkley, Browne, & Cacioppo, 2005;Pinquart & Sorenson, 2003), higher education (Savikko, Routasalo, Tilvis, Strandberg, & Pitkala, 2005), and higher income (Andersson, 1998;Savikko et al, 2005), whereas higher levels of loneliness are associated with living alone (Routasalo, Savikko, Tilvis, Strandberg, & Pitkala, 2006), infrequent contact with friends and family (Bondevik & Skogstad, 1998;Hawkley et al, 2005;Mullins & Dugan, 1990), dissatisfaction with living circumstances (Hector-Taylor & Adams, 1996), physical health symptoms (Hawkley et al, In press), chronic work and/or social stress (Hawkley et al, In press), small social network Mullins & Dugan, 1990), lack of a spousal confidant (Hawkley et al, In press), marital or family conflict (Jones, 1992;Segrin, 1999), poor quality social relationships (Hawkley et al, In press;Mullins & Dugan, 1990;Routasalo et al, 2006), and divorce and widowhood (Dugan & Kivett, 1994;Dykstra & De Jong Gierveld, 1999;Holmen, Ericsson, Andersson, & Winblad, 1992;Samuelsson, Andersson, & Hagberg, 1998).…”
Section: Structure and Spread Of Lonelinessmentioning
confidence: 99%
“…At the end of the 1990s, about one third (36%) of aged Finns ( 1 60 years, n = 1,037) experienced loneliness often or sometimes [12] . It is also known that loneliness is strongly associated with depression [13,14] , poor health status and impaired functioning [2] . In prospective studies, loneliness has predicted dementia [15] , increased use of health services [16] , early institutionalization [15] and impaired survival [17] .…”
mentioning
confidence: 99%
“…Many researchers have found a link between depression and shyness (Alfano, Joiner, Perry, & Metalsky, 1994;Anderson & Arnoult, 1985a, 1985bAnderson & Harvey, 1988;Traub, 1983) as well as between depression and loneliness (Andersson, 1985;Jackson & Cochran, 1991;Mullins & Dugan, 1990;Yang & Clum, 1994). Although some consider neither loneliness nor depression to be a direct cause of the other (Weeks et al, 1980), others have found that lonely and isolated people tend to be vulnerable to depression (Brown & Harris, 1978;Krietman, 1977;Rich & Bonner, 1987), that loneliness at the beginning of a semester predicted depression later in the semester (Rich & Scovel, 1987), and that experiencing feelings of loneliness at one point in time is significantly related to depression 3 years later (Green et al, 1992).…”
Section: Shyness and Lonelinessmentioning
confidence: 99%
“…Specifically, interventions should foster social support (Brage et al, 1993), provide enhanced opportunities for social contacts (Blai, 1989), and be directed at improving the lonely individual's links with others by providing settings where friendships may be easily formed (Weeks, 1994). Loneliness in older adults, therefore, could be somewhat relieved by placement in a residential setting where the individual's social network is facilitated by the proximity of neighbors and the establishment of apartment-ponsored activities (Mullins & Dugan, 1990). Seligson (1983) added that these activd ities should be noncompetitive in nature, such as volunteer work in hospitals and schools or perhaps group therapy, which provides multiple contacts with peers.…”
Section: Lonelinessmentioning
confidence: 99%